The Effectiveness of Islamic Guidance and Counseling to Reduce the Tendency of Juvenile Delinquency - Dzaki Aflah Zamani; Safiruddin Al Baqi (At-Ta'dib, 2019)
The process of searching for identity is not always easy for some teenagers. Sometimes they cannot act in accordance with the norms of their environment. They always want to try something new, tend to be more difficult and disorganized, and get the influence of their peers that they cannot refuse. This makes them unable to obey the norms or rules that exist in their schools. They are categorized as adolescents who have a tendency of delinquency because they violate school rules and have points on violation of discipline. The object of this research was carried out in one of the vocational high schools in Ponorogo, East Java. The study aims to determine the effectiveness of Islamic guidance and counseling to reduce the tendency of juvenile delinquency. This study used experimental design with nonequivalent control group design. Subjects of this study were 16 students who had tendency of juvenile delinquency (divided into experimental and control groups). Treatment for experimental group was eight sessions of Islamic guidance and counseling, while control group was conventional counseling. Analysis of Wilcoxon Signed-Rank Test from the pre-test and post-test experimental group showed significance value of 0.006 (<0.05). It shows that Islamic guidance and counseling is effective to reduce the tendency of juvenile delinquency.